Reduced Effectiveness and Comparable Safety in Biweekly vs. Weekly PEGylated Recombinant Human Growth Hormone for Children With Growth Hormone Deficiency: A Phase IV Non-Inferiority Threshold Targeted Trial - Chengjun Sun (Frontiers Media S.A., 2021)
ContextLong-acting recombinant human growth hormone (rhGH) has transformed growth hormone deficiency (GHD) treatment. However, the possibility and rationality for flexible time regimen are pending.ObjectiveWe studied the efficacy of biweekly versus weekly PEGylated rhGH (PEG-rhGH) therapy in GHD children.Design, Setting, and PatientsThis multicenter, phase IV trial with a non-inferiority threshold ≥20% enrolled 585 Tanner stage I GHD children.InterventionSubjects randomly received 0.20 mg/kg once-weekly or biweekly PEG-rhGH, or 0.25 mg/kg.w rhGH once daily for 26 weeks.Main Outcome MeasureThe primary outcome was height SD scores for chronological age (HtSDSCA) at week 26 and safety measurements including adverse events (AEs), IGF-2, and IGFBP-2 changes.ResultsAt week 26, the median HtSDSCA changed from −2.75, −2.82, and −2.78 to −2.31, −2.43, and −2.28 with weekly and biweekly PEG-rhGH, and daily rhGH, respectively. The difference in HtSDSCA was 0.17 ± 0.28 between weekly and biweekly PEG-rhGH, and 0.17 ± 0.27 between daily rhGH and biweekly PEG-rhGH, failing the non-inferiority threshold. Nevertheless, the height velocity of children receiving biweekly PEG-rhGH reached 76.42%–90.34% and 76.08%–90.60% that of children receiving weekly PEG-rhGH and daily rhGH, respectively. The rate of AEs was comparable among the groups. No statistical difference was observed in IGF-2 and IGFBP-2 levels among the groups. IGFBP-2 levels decreased over time in all groups, with no notable difference in IGF-2 and IGFBP-2 changes among the three treatment groups.ConclusionsAlthough notably promoted height velocity, biweekly PEG-rhGH failed the non-inferiority threshold as compared with either weekly PEG-rhGH or daily rhGH. Compared with short-term rhGH, long-acting PEG-rhGH did not significantly increase tumor-associated IGF-2 and IGFBP-2 expressions.Clinical Trial Registrationclinicaltrials.gov, identifier NCT02976675.